Good governance and professionalisation of non-profit sport clubs: a resource dependency perspective - Michäel Mrkonjic (Bern Open Publishing, 2023)
Whereas literature on non-profit sport organisations highlights a trend towards increased professionalization due to systemic expectations and pressure (Klenk et al., 2017), non-profit sport clubs still struggle with peculiar challenges related to the development their activities. They exist and develop thanks to an important contribution of voluntary staff driven by intrinsic motivation factors. Compared to for-profit companies or national sport governing bodies (NSGBs), they hardly rely on a competitive budget and they face financial vulnerability (Cordery et al., 2018). For instance, the mean budget for non-profit sport clubs in Switzerland is approx. CHF 60'000 (Lamprecht et al., 2017) whereas the budget of the umbrella federation, Swiss Olympic is approx. CHF 70 million (Swiss Olympic, 2019) and the mean budget of the affiliated NSGBs is approx. CHF 10 million (Kempf et al., 2019). Their capacity to respond to systemic pressure by resource acquisition and retention is limited. The good governance narrative emerged in the late1980s with the reform of the corporate and public sectors as a cure for mismanagement and unethical behaviour. In the field of sport, the concept became popular in the aftermath of corruption scandals in large international sport organisations and has led the creation of complex and demanding standards (Chappelet & Mrkonjic, 2019). To date, non-profit sport clubs are rather immune to good governance expectations and only a handful of initiatives that focus on the preservation of their social and economic impact address the topic (see Kirkeby, 2016). A reflection on their capabilities to effectively implement standards such as democracy or accountability is missing. This contribution investigates good governance and professionalization of non-profit sport clubs from a theoretical perspective. Starting with the hypothesis that non-profit sport clubs struggle to respond to systemic pressure because they lack resources and that acquiring and maintaining new resources is costly, this contribution builds on strategic management and resource dependency theory to analyse the challenges related to the implementation of good governance standards and develops strategic responses. References Chappelet, J. L. & Mrkonjic, M. (2019). Assessing sport governance principles and indicators. In M. Winand & C. Anagnostopoulos (Eds), Research Handbook on Sport Governance (pp. 10-28). Edward Elgar. Cordery, C. J., Sim, D. & Baskerville, R. F. (2018). Financial vulnerability in football clubs: Learning from resource dependency and club theories. Third Sector Review, 24(1), 49-70. Kempf, H., Weber, A. Ch., Zurmühle, C., Bosshard, B., Mrkonjic, M., Weber, A., Pillet, F., & Sutter, S. (2021). Leistungssport Schweiz - Momentaufnahme SPLISS-CH 2019 [Unpublished raw data]. Bundesamt für Sport BASPO. Kirkeby, M. (2016). Challenges and approaches to ensuring good governance in grassroots sport. In Transparency International (Ed.). Global Corruption Report: Sport (pp. 121-127). Routledge. Klenk, C., Egli, B., & Schlesinger, T. (2017). Exploring how voluntary sports clubs implement external advisory inputs. Managing Sport and Leisure, 22(1), 70-90. https://doi.org/10.1080/23750472.2017.1386587 Lamprecht, M., Bürgi, R., Gebert, A., & Stamm, H. P. (2017). Sportvereine in der Schweiz: Entwicklungen, Herausforderungen und Perspektiven. Bundesamt für Sport BASPO. Swiss Olympic. Budget 2019. https://www.swissolympic.ch/dam/jcr:274b8641-bb33-4296-bba0-133114146d96/Budget_2019_DE.pdf